1977
DOI: 10.2514/3.60663
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Finite-Difference Procedures for the Computation of Vortex Wakes

Abstract: Implicit finite-difference procedures for the primitive form of the incompressible Navier-Stokes and the compressible Euler equations are used to compute vortex wake flows. The partial differential equations in strong conservation-law form are transformed to cluster grid points in regions with large changes in vorticity. In addition to clustering, fourth-order accurate, spatial difference operators are used to help resolve the flowfield gradients. The use of implicit time-differencing permits large time steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In this sense we can relate the sign of eigenvalues with the upwind representation of the flow variables at the cell faces. The upwinding of the inviscid fluxes gives more freedom in devising implicit algorithms (Steger and Kutler [24] and Thomas and Walters [25]), since it loads up the diagonals of the implicit factors. Upwind differencing (Hartwich et al [26]), also, alleviates the necessity to add and to tune the numerical dissipation for numerical stability and accuracy as the schemes with central differencing that belong to the family of Beam and Warming Schemes (Beam and Warming [27]).…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In this sense we can relate the sign of eigenvalues with the upwind representation of the flow variables at the cell faces. The upwinding of the inviscid fluxes gives more freedom in devising implicit algorithms (Steger and Kutler [24] and Thomas and Walters [25]), since it loads up the diagonals of the implicit factors. Upwind differencing (Hartwich et al [26]), also, alleviates the necessity to add and to tune the numerical dissipation for numerical stability and accuracy as the schemes with central differencing that belong to the family of Beam and Warming Schemes (Beam and Warming [27]).…”
Section: Numerical Simulationmentioning
confidence: 99%
“…There were a number of early groundbreaking applications coming from the CFD Branch at NASA Ames. Steger and Kutler [15] used the Beam-Warming implicit finite-difference procedures for the computation of unsteady vortex wakes. Kutler et al [13] applied the Beam-Warming schemes to viscous supersonic flow over symmetrical and asymmetrical external axial corners.…”
Section: Applications Of Beam-warming Approximate Factorization Algormentioning
confidence: 99%
“…Several previous studies of two-dimensional vortex interaction show the distortion of the vortex cores into an ellipse caused by the strain rate field of one vortex action upon the other, (Moore and Saffman [52], Rossow [59,60], Steger and Kutler [64], Christiansen and Zabusky [12], Melander et al [46,47]). Melander et al [46] depict the flow of co-rotating vortices as observed from a frame of reference rotating with the vortex cores.…”
Section: Introductionmentioning
confidence: 96%